Asrij/OCIAD1 contributes to age-associated microglial activation and neuroinflammation in mice - Dongre, Prathamesh; Ramesh, Madhu; Govindaraju, Thimmaiah; Inamdar, Maneesha S. (Frontiers in Aging Neuroscience, 2025)
Aging is characterized by chronic low-grade neuroinflammation, which increases the risk of neurodegenerative disorders. Neuroinflammation, driven by the activation of astrocytes and microglia, underlies age-associated cognitive deficits. Amplified neuroinflammatory responses to immune challenges are attributed to microglial activation in the aged brain. Despite extensive clinical and experimental evidence linking neuroinflammation to aging, the molecular players that control age-associated neuroinflammatory responses in the brain are not fully understood. Genome-wide association studies (GWAS), proteomics, and transcriptomic datasets have revealed that Asrij/OCIAD1 is a novel aging and Alzheimer’s disease (AD)-associated factor. Asrij levels are increased in patients with AD and are known to promote amyloid-beta (Aβ) pathology and microglia-mediated neuroinflammation, which are associated with cognitive dysfunction in AD. Increased levels of Asrij are also reported in the brains of aged wild-type (WT) mice; however, whether this may promote neuroinflammation or be a protective response during aging is not known. To test this, we used young and aged WT and asrij KO mice and showed that normal aging is associated with increased microgliosis and astrocyte activation in WT mice. While young asrij KO mice do not display any differences in glial activation, aged KO mice have reduced microglial and astrocytic activation compared to aged WT mice. This is accompanied by reduced levels of pro-inflammatory mediators and downregulation of STAT3 and NF-κB signaling in the cortex and hippocampus of aged asrij KO mice. Additionally, asrij depletion inhibits LPS-induced microglial activation and neuroinflammation in aged mice. This indicates that Asrij is essential for the neuroinflammatory responses in the brains of aged mice. We propose that identifying pharmaceutical modulators of Asrij could provide novel means to control microglial activation and neuroinflammation during normal aging.